2017
DOI: 10.5812/ijcm.5921
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Risk of Breast Cancer: A Systematic Review and Meta-Analysis in Iran

Abstract: Background: Various studies in Iran on the role of BMI higher than normal (BMI ≥25) on breast cancer have reported different results.Objective: The aim of this systematic review and meta-analysis is to estimate the odds ratio of overweightness and obesity as risk factors of breast cancer in studies conducted in Iran.Evidence Acquisition: The following main databases were searched from 2004 to 2014 to find related articles: PubMed, Web of Science, Google Scholar, Scopus and Iranian databases (SID and Magiran), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Our results indicate a 63.0% increase in the number of new breast cancers among females between 2016 and 2025. A rising prevalence of obesity 25,26 as a risk factor for breast cancer in Iranian women 28,29 may partly explain the rise, while late age at first pregnancy, nulliparity and a limited duration of breast feeding may also increase breast cancer risk. 30,31 The most notable shifts observed for reproductive factors in Iranian women were declines in parity and older age at the first pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate a 63.0% increase in the number of new breast cancers among females between 2016 and 2025. A rising prevalence of obesity 25,26 as a risk factor for breast cancer in Iranian women 28,29 may partly explain the rise, while late age at first pregnancy, nulliparity and a limited duration of breast feeding may also increase breast cancer risk. 30,31 The most notable shifts observed for reproductive factors in Iranian women were declines in parity and older age at the first pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 , 2 ] In 2012, the International Agency for Research on Cancer reported 1.7 million breast cancer new cases, with 6.3 million new patients diagnosed in the previous 5 years. [ 3 ] Every year, almost 1.5 million women worldwide are diagnosed with breast cancer. [ 4 ] Breast cancer is a type of metastatic cancer that can spread to other parts of the body, including the bones, lungs, liver, and brain, making it uncurable.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Overweight, lack of physical activity, and obesity have been identified as the major risk factors in high and middle-income nations, accounting for 18%. [ 3 ] Multiple research relates it to the fact that adipocytes cause chronic inflammation in obesity leading to a rise in the systemic levels of cytokines as interleukin 6 and tumor necrosis factor. [ 10 ] Obesity is a known risk factor for metabolic syndrome, type 2 diabetes, and heart attacks [ 11 ] ; the latter is still the leading cause of death in women with early-stage breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…There are legion risk factors related to breast cancer such as: age, genetic background, hormonal condition, obesity, exposure to radiation and chemical carcinogens. Histopathological markers, including the expression of sex hormone receptors and human epidermal growth factor receptor (HER2) are commonly used as diagnostic means to contribute to choosing an effective approach in clinical treatment (3)(4)(5)(6). Almost 60 to 70 % of breast cancer cases are ER/PR positive and so tumor growth is dependent on estro-gen. And also, 20 to 25 % over-express Her2, which are more aggressive (7,8).…”
Section: Introductionmentioning
confidence: 99%